The timed barium swallow and its relationship to symptoms in achalasia: Analysis of surface area and emptying rate. Issue 12 (23rd June 2020) - Sanagapalli, Santosh; Plumb, Andrew; Maynard, John; Leong, Rupert W.; Sweis, Rami
Abstract: Background: Timed barium swallow (TBS) is used to objectively measure response following achalasia therapy; however, findings can be discordant with symptoms. We hypothesized that measurement of surface area of the residual barium column would improve its utility in measuring outcome. Methods: In a single‐center cohort, achalasia patients undergoing therapy between September 2015‐2016 who had TBS were included. Four metrics of emptying were studied: Post‐therapy residual barium (a) absolute height and (b) surface area and percentage reduction in (c) residual height (%H) and (d) surface area (%SA) compared to pretherapy. Metrics were evaluated against symptom response (Eckardt score). Key Results: Twenty‐four achalasics (median age 43 year; 13 males) were included; 14 received pneumatic dilatation, and 10 had peroral endoscopic myotomy. Treatment resulted in significant reduction in median Eckardt score (7 to 1; P = .03), mean residual barium column height (14.7 ± 8.7 to 7.9 ± 6.0 cm; P = .01) and surface area (52.7 ± 43.5 to 24.5 ± 23.6 cm 2 ; P = .02). There were 4 (17%) initial non‐responders (Eckardt > 3). % SA was best at discriminating between responders and non‐responders (area under curve 0.85 ± 0.08; sensitivity 100%, specificity 80%). Concordance with symptomatic response following therapy was 83% when using 45% as the cutoff for surface area reduction compared to pretherapy. Eight patients whose static barium height was discordant with symptoms became concordant when % SA was used as a measure of response. Conclusions & Inferences: Change in barium surface area is a superior measure of esophageal emptying and better correlates with treatment response than the conventional 5‐minute barium height in defining objective response to achalasia therapy. Abstract : When interpreting the timed barium swallow image, the surface area of the residual column better reflects the adequacy of esophageal emptying compared to the column height.